Management of diabetic ketoacidosis in children: Does early insulin glargine help improve outcomes? - Rebecca Ohman‐Hanson; G. Todd Alonso; Laura Pyle; Ryan McDonough; Mark Clements (Journal of Diabetes, 2024)
Abstract Background Rebound hyperglycemia following the resolution of diabetic ketoacidosis (DKA) is common in pediatric patients with type 1 diabetes, increasing the risk of recurrent DKA and complicating the transition to subcutaneous insulin. Multiple studies suggest that early administration of long‐acting insulin analogs during DKA management safely improves this transition. Objective This study aimed to determine whether early insulin glargine administration in children with DKA prevents rebound hyperglycemia and recurrent ketosis without increasing the rate of hypoglycemia or hypokalemia. Methods Patients aged <21 years presenting with DKA to Children's Mercy Kansas City between October 2012 and October 2016 were reviewed. They were categorized as Early (>4 h of overlap with intravenous [IV] insulin) and Late (<2 h of overlap) cohorts. Results We reviewed 546 DKA admissions (365 Early and 181 Late). Rebound hyperglycemia (>180 mg/dL) was lower in the Early group (66% vs. 85%, p ≤ 0.0001). Hypoglycemia (<70 mg/dL) during IV insulin administration was higher in the Early group than in the Late group (27% vs. 19%, p = 0.042). Hypoglycemia within 12 h of IV insulin discontinuation was lower in the Early group (16% vs. 26%, p = 0.012). Recurrent ketosis, hypokalemia, and cerebral edema were not different between the groups. Conclusions Early glargine administration in pediatric DKA management is safe, decreases the rate of rebound hyperglycemia, and improves the transition to subcutaneous insulin. Hypoglycemia is less frequent following IV insulin discontinuation with early glargine, but the IV insulin rate may need to be reduced to minimize hypoglycemia during IV insulin infusion.